2018
DOI: 10.1002/cam4.1542
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact of the inflammation‐based indices in colorectal cancer patients with adjuvant chemotherapy

Abstract: Increasing evidences reported that cancer‐triggered inflammation was associated with survival prognosis from colorectal cancer (CRC). However, the comprehensive effects of inflammatory‐based coNLR‐PLR that combines neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) rarely remain to be determined during chemotherapy. We retrospectively analyzed clinical data and baseline laboratory parameters from 153 colorectal cancer patients who underwent palliative adjuvant chemotherapy between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In our study we did not count the NLR of the healthy population, but we refer to Professor Tao's study and think that the NLR of the healthy population is 0.62 to 1.64, and the PLR of the healthy population is 45.81 to 108.33. [ 11 ] As summarized in Table 1 , an increased NLR level was significantly associated with age ( P = .008), liver metastases ( P < .001), H pylori infection ( P = .008), peritoneal metastasis ( P = .003). The PLR was associated with liver metastasis ( P = .021), sex ( P = .048), and with H pylori infection ( P = .008), which was not associated with age, HER-2, CA-199 level, metastatic sites, and left cervical lymph node metastases.…”
Section: Resultsmentioning
confidence: 99%
“…In our study we did not count the NLR of the healthy population, but we refer to Professor Tao's study and think that the NLR of the healthy population is 0.62 to 1.64, and the PLR of the healthy population is 45.81 to 108.33. [ 11 ] As summarized in Table 1 , an increased NLR level was significantly associated with age ( P = .008), liver metastases ( P < .001), H pylori infection ( P = .008), peritoneal metastasis ( P = .003). The PLR was associated with liver metastasis ( P = .021), sex ( P = .048), and with H pylori infection ( P = .008), which was not associated with age, HER-2, CA-199 level, metastatic sites, and left cervical lymph node metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Although the integration of NLR and PLR as a composite biomarker has been widely investigated, comparisons between the results of different studies are difficult due to diverse cutting points selected (38, 45). For instance, Tao and colleagues found a strong predictive effect for combined NLR-PLR index in 153 patients with CRC who received adjuvant chemotherapy (46). Feng et al also found that INP was an independent prognostic marker in patients with EC without neoadjuvant or adjuvant treatment (47).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increasing monocytes and lymphatic cells would enhance the resistance against tumor invasion[11]. Increasing evidence shows that an elevated neutrophil-to-lymphocyte ratio (NLR) is closely related to a poor prognosis in ovarian cancer, cholangiocarcinoma, and elective colorectal cancer (CRC)[12-14]. The overexpression of circulating derived NLR, an effective biomarker for the diagnosis of early pancreatic cancer[15], was accompanied by increasing distal organ invasion in metastatic CRC[16].…”
Section: Introductionmentioning
confidence: 99%
“…An elevated preoperative lymphocyte-to-monocyte ratio (LMR), as a superior existing biomarker, was positively correlated with the survival outcomes of patients with resectable CRC and presented better overall survival[17]. Other inflammatory indexes, such as the platelet-to-lymphocyte ratio (PLR)[14] and systemic immune inflammation index (SII)[18], have also been studied in the exploration of optimal predictive models for tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%